Russian sub-national actors: paradiplomacies in the Arctic region - Alexander Sergunin (European Regional Science Association (ERSA), 2014)
The paper aims at examining Russian sub-state units' Arctic 'foreign policies'. The paper starts from discussing which theories are applicable to explaining the phenomenon of paradiplomacy. Particularly, the paper focuses on the following strategies/methods of paradiplomacy: making direct agreements with international partners; attracting foreign investment; creating regions' positive image; cooperation with international organizations; establishing representative offices in foreign countries; city-twinning; participation in Euroregions and other sub-regional arrangements; capitalizing on national diplomacy and federal infrastructures, etc. The institutional framework available for the sub-state actors in the Arctic region is examined. The implications of paradiplomacy for Russia's Arctic strategy are analyzed.
Keywords: F59; H77; 330; subnational units; Russia; paradiplomacy; Arctic